Komunikasi interpersonal antar mahasiswa ntt dengan mahasiswa lain daerah di fakultas ilmu komunikasi universitas dr. Soetomo surabaya - Chabibulloh, Dzikri; Prasetyo, Iwan Joko (Soetomo Communication and Humanities, 2020)
Through interpersonal communication, a person can convey what is in the mind's mind to others both directly and indirectly. As is the case with students from NTT with other students in the area at the University of Dr. Soetomo in particular the Faculty of Communication Sciences. By trying to communicate with other students, of course they have various ways or communication that must be done. The purpose of this study is to describe and explain the interpersonal communication of NTT students with other regional students at the University of Dr. Soetomo Surabaya. The research method used in this research is descriptive using qualitative research approaches. From the results of research conducted, it is known the interpersonal communication stage of NTT students with other regional students at the University of Dr. Soetomo Surabaya, where an individual is in the social and cultural life of others so that the concept of adjustment that must be done by NTT students comes when communicating. The process of individual experiences in interpersonal communication with others makes thoughts, self, and emotions on the topic of communication that will cause socio-cultural conditions between individuals with other individuals different meanings.Keywords: communication; interpersonal; student.